Peran Struktur Modal terhadap Profitabilitas dengan Good Corporate Governance (GCG) sebagai Variabel Moderasi - Waruwu, Merniwati; Satriawan, Bambang; Sumantri, Sumantri; Diah Lestari, R.A. Widyanti (Program Studi Pendidikan Akuntansi Fakultas Ekonomika dan Bisnis Universitas Negeri Surabaya, 2025)
In this study Good Corporate Governance (GCG) as a moderation variable between capital structures to profitability in BEI, that is the goal for this analysis. Debt Asset Ratio (DAR) and Debt to Equity Ratio (DER) are used as capital structure gauges, while Return On Asset (ROA) is used to measure profitability. Indicators such as Audit Committee, Managerial Ownership, Institutional Ownership and Independent Commissioner are four GCG indicators. The technique for the use of the sample is purposive sampling with the amount studied by 12 banks, secondary data with which analysis using 17 stata. The result is significant positive measurement indicated by DAR to ROA, the positive result is not significant shown DER to ROA. Independent Commissioner strengthens and significant between DAR against ROA, and also weakens insignificant between DER against ROA. Other GCG indicators cannot moderate.